YouTube marketing - Eagle, Will (Hoboken, NJ John Wiley & Sons Inc., 2019)
YouTube is the top destination for online video. With over a billion viewers around the globe, it's also valuable real estate for marketers looking to get their message out. YouTube Marketing For Dummies shares insight from a former YouTube employee who helped large and small businesses create effective marketing campaigns.
Keywords: YouTube (Electronic resource).; Internet marketing; Internet videos; Online social networks